Representasi Nilai-Nilai Karakter Sebagai Role Model dalam Film â€œArbainâ€ : Sebuah Analisis Semiotik - Fathor Rozi; Baharun, Hasan; Badriyah, Nurul (TADRIS: Jurnal Pendidikan Islam, 2021)
This study aims to determine and analyze the representation of moral values â€‹â€‹as role models. This research is included in the qualitative approach research using the Semiotics Analysis technique which was initiated by Roland Barthes. Arbain’s film as an object of research with content analysis techniques that focus on its moral values â€‹â€‹combined with the religious values â€‹â€‹contained in it, both of which are one unit. From this research, the results obtained include religious values â€‹â€‹contained examples in studying the history of the Prophet, the obligation to seek knowledge, taking ablution, praying in congregation and the power of a prayer. While the social values â€‹â€‹that we can learn are always alert in helping, smiling as a noble personality, greeting early, loving Muslim brothers and practicing wise leadership values. This Arbain film is very worthy to be used as an example and watched by a wide audience with the hope that the values â€‹â€‹of the teachings of the role model of the Prophet Muhammad can be conveyed in a simple way and can be well received by our children and the wider community in general